3x-11=-3x+7

Simple and best practice solution for 3x-11=-3x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-11=-3x+7 equation:


Simplifying
3x + -11 = -3x + 7
Reorder the terms:
-11 + 3x = -3x + 7
Reorder the terms:
-11 + 3x = 7 + -3x
Solving
-11 + 3x = 7 + -3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation.
-11 + 3x + 3x = 7 + -3x + 3x
Combine like terms: 3x + 3x = 6x
-11 + 6x = 7 + -3x + 3x
Combine like terms: -3x + 3x = 0
-11 + 6x = 7 + 0
-11 + 6x = 7
Add '11' to each side of the equation.
-11 + 11 + 6x = 7 + 11
Combine like terms: -11 + 11 = 0
0 + 6x = 7 + 11
6x = 7 + 11
Combine like terms: 7 + 11 = 18
6x = 18
Divide each side by '6'.
x = 3
Simplifying
x = 3

You can always share this solution

See similar equations:

| 2t-6=3t+21 | | 6(8-x)=90 | | -3(3-3r)+7(3r+7)=-20 | | 17.3+v=22.32 | | 3+5x(7-2)=16+5x | | 1.8x=40.14 | | 5(m-1)+m=72 | | (5-6x)/3 | | 6x+4+52= | | 63x^2+74x-9=0 | | x+3-2x=15+x | | -16f=-15f+18 | | 7x+12-9x=16-19x+17x-4 | | (x-6)-(x+2)=5x | | 4x+1=100-7x | | 25x-9-14x+3=24x-3-13x+15 | | -14u=-15u-18 | | 6x+5=7(x-6) | | 4(y+4)=5y+16 | | 1x+21=3 | | A-4/11=2 | | 1=2x+2x-7 | | 4x^2-5x-3=2x^2-3x | | 6y^4-36y^3+54y^2=0 | | 8t^2+44t+48=0 | | 6(5-w)=26 | | 19r=90 | | 9+4x+4x=9 | | -12+3n=-(2n+7) | | 2500x-15000=5000(12-x)^1/2 | | 6(5-w)=35 | | 2(-6x-4)-2(-3x+6)=-26 | | f(x)=l-x+3I | | 6x+12-3x=36 | | 2.4y=4.66y+5.236 | | 6x-10x=-20-12 | | f(x)=l-x+3 | | 112.5/125 | | 2(x-1)+4x=2(-1)+2 | | -14=8n | | 55=X/5 | | x+7y=343 | | 2(b-3)-3=3(b-6) | | 6n^2-4n-10=0 | | -4(6+2x)=-32 | | 78=21/x=8/× | | 2/3=5(y-0.2 | | 38-14=41-x | | y=3x(x-3) | | 2x-20+3x+10=180 | | y=5(6.33-1.67y)-13 | | 9p=10p+9 | | 4v+2=9v+6-v | | 10u^7+26u^6-12u^5=0 | | -t-10=-6t+10 | | N=(-5/-3)(4/2) | | 8+8d=-6+6d | | -13+3x=11+x | | k=2k-5 | | (5/0)(25/12) | | -2x-7=6x-63 | | 5/14•C=1/2 | | 2-2m=-3m+10 | | 6c-4-C=24 | | 0=3x(x-3) |


Related pages


what is 0.375 as a fraction8x x 3complex fractions calculator with stepswhat is the prime factorization of 97common multiples of 6gcf of 64 and 48fraction divided by a fraction calculatorfactor x2 2x 1derivative caculatorleast common multiple fractions calculator6a squaredprime factorization chart 1-1000sinx cosx derivativeroman numerals 94graph the equation 3x-2y 64y 5y0.33333 as a fractionmultiplication of fraction calculatorhow to write a prime factorizationsin3x formulaprime factorization of 66factor 2x2 5x 12finding the lcm calculator2x 6y 12derivative of piesolving mixed fractions calculatorroman numerals conversion7x 4y 16solve 5x5solving multi step equations calculatorwhat is the prime factorization of 124how to write 1984 in roman numeralssolve quadratic calculatorwhat is 3.75 as a fraction in simplest form1yfhow do you write 1000 in roman numeralsy 2sin2xmath derivative solverderivative of tanx 2x 4y graphcotangent of 0least common denominator generator724.6derivative of lnx lnxgcf of 96 and 144111-11111939 in roman numeralscotx tanxderivative of sin sinx3y x 3x 2 12x 4 0can x 3 1 be factoredsqrt 625convert 1.25 to a percent15000 rupees in dollarswhat is the lcm of 2 and 3y 2cosxhrtv1what is 375 as a decimalfactor 9x 2 16what is the prime factorization of 45lowest common denominator calculator fractions2004 roman numeralsroman numerals x1cos40747-1000how to graph x 3yy 2 sinx16 qt galgcf of 96 and 108lcm of 2 and 2factor 3x 2-2x-5